2020
DOI: 10.1111/basr.12192
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress in organizations: Types, antecedents, and consequences

Abstract: Research indicates that the well‐being and productivity of over 100 million people in the global workforce may be compromised by posttraumatic stress (PTS). Given that work‐related experiences are often the source of the trauma that leads to PTS, and that PTS due to any cause can interfere with employees’ job performance, organizations would do well to consider the antecedents and consequences of PTS. This review of research—primarily within fields adjacent to business—on the types, antecedents, consequences, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 116 publications
0
7
0
Order By: Relevance
“…In order to lessen problems related to spurious relationships, age, sex, working region, tenure, and number of patients who had died from COVID-19 were statistically controlled in hypotheses testing. Recently, Williams and Williams ( 2020 ) suggested that personal and occupational characteristics may represent important risk factors in developing PTS symptoms. Specifically, Williams and Williams ( 2020 ) reported that younger age, being male, and a high job tenure appear to lower workers' risk of developing PTS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to lessen problems related to spurious relationships, age, sex, working region, tenure, and number of patients who had died from COVID-19 were statistically controlled in hypotheses testing. Recently, Williams and Williams ( 2020 ) suggested that personal and occupational characteristics may represent important risk factors in developing PTS symptoms. Specifically, Williams and Williams ( 2020 ) reported that younger age, being male, and a high job tenure appear to lower workers' risk of developing PTS.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Williams and Williams ( 2020 ) suggested that personal and occupational characteristics may represent important risk factors in developing PTS symptoms. Specifically, Williams and Williams ( 2020 ) reported that younger age, being male, and a high job tenure appear to lower workers' risk of developing PTS. Furthermore, many scholars suggested that women appear more likely than men to engage in behavioral expression of emotions, such as crying (Nolen-Hoeksema and Jackson, 2001 ).…”
Section: Methodsmentioning
confidence: 99%
“…Fundamentally, all organizations should give some forethought to events that could be traumatic. In the same way that organizations should plan for disasters – and perhaps as part of the same preparation effort (Williams and Williams, 2020) – they should identify resources for professional care of organization members who become traumatized or who have other mental health care needs. Large organizations with health insurance coverage or employee assistance programs that can assist organization members should strive to make all personnel aware of those resources.…”
Section: Discussionmentioning
confidence: 99%
“…The model this paper has presented also has many implications for future research. The most significant implications have to do with the risks of errors when cumulating research on ASD, PTSD and cPTSD to draw conclusions about “posttraumatic stress” or “PTS” (Vogel and Bolino, 2019; Williams and Williams, 2020). First, despite their many similarities, certain symptoms are more pronounced in each type of condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation